Deciphering the role of DOCK8 in tumorigenesis by regulating immunity and the application of nanotechnology in DOCK8 deficiency therapy - Zhang, Longhui; Cao, Yang; Dai, Xiangpeng; Zhang, Xiaoling (Frontiers in Pharmacology, 2022)
The DOCK8 immunodeficiency syndrome is a severe immune disorder and characterized by serum IgE levels elevation, fungal and viral infections, dermatitis and food allergies. It was well known that DOCK8 is crucial for the survival and function of multiple immune related cells. However, the critical role of DOCK8 on tumorigenesis through regulating immunity is poorly investigated. Accumulating evidences indicated that DOCK8 could affect tumorigenesis by regulating the immunity through immune cells, including NK cells, T cells, B cells and dendritic cells. Here, we summarized and discussed the critical role of DOCK8 in cytoskeleton reconstruction, CD4+ T cell differentiation, immune synaptic formation, tumor immune infiltration, tumor immune surveillance and tumorigenesis. Furthermore, the potential roles of nanotechnology in improving the hematopoietic stem cell transplantation-based therapy for DOCK8 deficiency diseases are also highlighted and discussed.